Linking collaborative supplier social sustainability practices and supplier performance in asymmetric power relationships with buyers - Dariusz Siemieniako (Journal of Business Economics and Management)
This article objective is to identify factors related to collaborative supplier social sustainability practices and supplier international performance, and to propose a set of propositions regarding their relationships within a conceptual model. The research context includes manufacturing companies of various sizes located in Poland, which are predominantly Polish-owned and act as suppliers to large foreign buyers in relationships characterized by power asymmetry. The study determines which operationalizations of the main factors should be retained through factor extraction, evaluates their internal consistency using exploratory factor analysis, and validates the control variables. The conceptual model distinguishes between two areas of supplier collaboration on social sustainability practices: supply chain collaboration and horizontal collaboration. Future research may focus on examining the direct impact of these forms of collaboration on suppliers’ financial and non-financial performance in the context of their international operations.